Hydrogen Isotope Separation Using a Metal–Organic Cage Built from Macrocycles. Issue 32 (4th July 2022) - He, Donglin; Zhang, Linda; Liu, Tao; Clowes, Rob; Little, Marc A.; Liu, Ming; Hirscher, Michael; Cooper, Andrew I.
Abstract: Porous materials that contain ultrafine pore apertures can separate hydrogen isotopes via kinetic quantum sieving (KQS). However, it is challenging to design materials with suitably narrow pores for KQS that also show good adsorption capacities and operate at practical temperatures. Here, we investigate a metal–organic cage (MOC) assembled from organic macrocycles and Zn II ions that exhibits narrow windows (<3.0 Å). Two polymorphs, referred to as 2α and 2β, were observed. Both polymorphs exhibit D2 /H2 selectivity in the temperature range 30–100 K. At higher temperature (77 K), the D2 adsorption capacity of 2β increases to about 2.7 times that of 2α, along with a reasonable D2 /H2 selectivity. Gas sorption analysis and thermal desorption spectroscopy suggest a gate‐opening effect of the MOCs pore aperture. This promotes KQS at temperatures above liquid nitrogen temperature, indicating that MOCs hold promise for hydrogen isotope separation in real industrial environments. Abstract : Metal–organic cages (MOCs), built from macrocycles, were investigated for the first time for the separation of hydrogen isotopes. The MOC crystal has flexible narrow pores, which leads to a separation temperature of over 100 K even without existing strong adsorption sites.